Direct steam generation in linear solar concentration: Experimental and modeling investigation – A review - de Sá, Alexandre Bittencourt; Pigozzo Filho, Victor César; Tadrist, Lounès; Passos, Júlio César (Renewable & sustainable energy reviews, 2018)
The present work gathers the main studies in the field of linear solar concentration operating at direct steam generation and gives a comprehensive state of the art. It discuss the direct steam generation operational strategy and advantages, and presents a brief introduction to the two-phase flow phenomena. This review shows an overview of the main experimental studies performed in the area, alongside models found in the literature. It presents the main considerations and conclusions of each model. The type of work performed by the authors is divided into sections: experimental, one-dimensional models, light water reactor evaluation software, among others. Even though direct steam generation in solar concentrators is a relatively new concept, it has been properly studied and proved to be a viable operational strategy for both new solar power plants and to generate steam for industrial heating. However, further studies on this subject must be performed. All the works here gathered may serve as a basis for these new studies. •Direct Steam Generation is when steam is generated directly in the solar field.•This process has both industry and power generation applications.•This review gathers a large number of experimental and theoretical works.•The main considerations and conclusions of each work analyzed are highlighted.•Historical development and the future of this technology are discussed.